Pelatihan Konseling bagi Kader untuk Kelompok Kerja Operasional Posyandu (Pokjanal Posyandu) - Israini Suriati; Andi Sitti Umrah; Nailul Hikma; Rusadi (JPM: Jurnal Pengabdian Masyarakat, 2024)
The method used in participatory action service activities involves Posyandu cadres as the main subject. The aim of this service is to contribute to improving the quality of health services and community services at the posyandu level, including; improving counseling skills, increasing health awareness, improving communication, increasing community involvement, improving the quality of posyandu services and increasing community independence. Training is carried out through an interactive and participatory approach, with a focus on developing counseling skills, effective communication, and handling public health problems. The results of the service show a significant increase in Posyandu cadres' understanding of the concept of counseling and its application in Posyandu operational activities. Posyandu cadres who took part in the training showed increased ability to detect public health problems, provide emotional support, and design appropriate interventions. The implementation of these counseling skills in the Posyandu operational working group in Palopo City has had a positive impact on interactions between cadres and the community, increasing cadres' confidence in providing health information, and strengthening community involvement in disease prevention efforts. Counseling training for Posyandu cadres in Palopo City can be used as a model for developing similar programs in other areas. By strengthening cadre capacity, it is hoped that health services at the community level can be more effective and have a positive impact on improving the health status of the community as a whole.